2005
DOI: 10.5194/acp-5-77-2005
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous conversion of NO<sub>2</sub> and NO on HNO<sub>3</sub> treated soot surfaces: atmospheric implications

Abstract: Abstract. In the present study, the heterogeneous conversion of nitrogen oxide (NO) and nitrogen dioxide (NO 2 ) was studied at atmospheric humidity levels on flame soot surfaces treated with gaseous nitric acid (HNO 3 ). In addition, the heterogeneous reaction of HNO 3 on soot was investigated at atmospheric humidity.For the treatment of soot by pure HNO 3 only reversible uptake with a surface coverage of ∼1-2×10 14 HNO 3 cm −2 was observed for HNO 3 mixing ratios in the range 250-800 ppbv. Only for higher HN… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
60
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(64 citation statements)
references
References 36 publications
4
60
0
Order By: Relevance
“…Studies using different vehicles and engine tests have shown that HONO to NO x emission ratios range from 0.01% to 1.8% (Kurtenbach et al, 2001), depending on the vehicle and fuel type, and the oxygen content. Generally, diesel vehicles under rich operation conditions lead to higher HONO/NO x ratios than gasoline-fuelled vehicles under lean operation conditions (Kurtenbach et al, 2001).…”
Section: Hono Emissionsmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies using different vehicles and engine tests have shown that HONO to NO x emission ratios range from 0.01% to 1.8% (Kurtenbach et al, 2001), depending on the vehicle and fuel type, and the oxygen content. Generally, diesel vehicles under rich operation conditions lead to higher HONO/NO x ratios than gasoline-fuelled vehicles under lean operation conditions (Kurtenbach et al, 2001).…”
Section: Hono Emissionsmentioning
confidence: 99%
“…Heterogeneous conversion of nitric acid (HNO 3 ) on primary organic aerosols (Ziemba et al, 2010) or ground surfaces (RiveraFigueroa et al, 2003) yields HONO, however those reactions have been recently discredited under atmospheric conditions (Kleffmann et al, 2004;Kleffmann and Wiesen, 2005). Other works (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, a heterogeneous reaction of HNO 3 on soot (R1) was proposed to explain the overestimation of HNO 3 / NO x in simulations (Rogasi et al 1997). This mechanism has been successfully applied in some studies, although it has still to be confirmed in laboratory studies (Hauglustaine et al 1996;Kleffmann and Wiesen 2005). Many uptake coefficients for R1 (γ HNO3 ), ranging from 10 −7 to 10 −2 , have been proposed based on laboratory and model experiments (Hauglustaine et al 1996;Rogasi et al 1997), and therefore studies of γ HNO3 that are appropriate for the soot aerosol morphology in China are needed.…”
Section: Introductionmentioning
confidence: 99%